Formulation of a comprehensive Model of family court system in Malaysia: towards an effective family disputes resolution - Che Soh @ Yusoff, Roslina (2014)

(untitled)
This study examines the feasibility and the practicality of establishing the family courts in Malaysia within the existing legal system that practices dual jurisdiction when dealing with family law matters. The emphasis is made on the system of administration, facilities as well as family adjudication system where mediation, counseling and arbitration are fully utilised to resolve the disputes. The main purpose of this study is to propose for a more suitable and conducive system of adjudication when dealing with family related disputes. Comparative analysis is adopted in this study when examining the strength and weaknesses of the existing courts system in Malaysia and the family court system in other jurisdictions such as Australia and Singapore. The study concludes that the family court which is intended to be established in Malaysia should be consistent with existing models as practised in other jurisdictions. The court structure must be a specialized court with specialized and trained officers, it promotes less adversarial trial or inquisitorial approach, it encourages harmonious, effective dispute resolution through mediation and it also collaborates with social service agencies and welfare organizations that provide counseling and therapeutic approaches to resolve family disputes. By taking into consideration the unique characteristic of family law system in Malaysia, the family court structure is proposed to be streamlined within the existing civil and Syariah courts’ jurisdiction.